Khittah Perjuangan Muhammadiyah dan Implementasinya di Berbagai Daerah di Indonesia - Lady Maysuri Ma’rufi; Muliadi .; Nurwan Patilima; Wahyu Andini; Abbas Baco Miro; Ahmad Nashir (CV. ITTC INDONESIA, 2026)
The Muhammadiyah Struggle Principles (Khittah Perjuangan Muhammadiyah) is a grand strategic framework that serves as an ideological guideline, movement direction, and the basis for Muhammadiyah organizational policies in realizing a True Islamic Society. This article aims to analyze the philosophical foundation, historical development, and contextual implementation of the Muhammadiyah Struggle Principles (Khittah Perjuangan Muhammadiyah) in various regions in Indonesia. This research uses a qualitative descriptive approach through literature review and document analysis of various Khittah formulations, including the Twelve-Year Steps, the Palembang Khittah, the Ujung Pandang Khittah, and the Denpasar Khittah. The results of the study indicate that the Khittah functions as a theory of struggle as well as a basic policy pattern that allows Muhammadiyah to maintain ideological consistency while remaining adaptive to socio-political changes. The implementation of the Khittah through the Muhammadiyah Enterprises (AUM) in the fields of education, health, and social society reflects a moral political strategy (high politics), civil empowerment, and inclusive and humanity-oriented community da'wah practices.